Investigations into the Conductance, Micellization and Dissociation Behaviour of Zinc Soaps in 70/30 Benzene-Methanol Mixture - Upadhyaya, S.K.; S. Sharma, Prem. (Asian Journal of Chemistry, 2010)
The conductance of zinc caprylate and laurate was measured in 70/30 benzene-methanol mixture at several temperatures. The values of the CMC increase with an increase in temperature. The dissociation constant, degree of dissociation and limiting molar conductance were evaluated from conductivity measurements. The results showed that these soaps behaved as weak electrolytes in dilute solutions and the micellization process was dominant over the dissociation process.